Political Dimensions of Kejawen in Hegemonic Islamic Society - Wasisto, Muhammad Adiz (Riwayat: Educational Journal of History and Humanities, 2023)
Kejawen and its community often depicted as having no political dimensions in relevant to Indonesian political scene. However, political discourse related to Kejawen and its community has been started and developed since the collapse of Majapahit kingdom in the late 15th century. The political dimensions of Kejawen revolves around the struggle to resist political Islam and Islamization. This paper intends to showcase the Kejawen political dimension vis a vis to Islamic hegemony that would inform the reader how Kejawen and fundamental Islam interact in public sphere. This research article employs qualitative methods which tried to analyze and categorize the topic in which the political dimension of Kejawen appears. This research article uses wide ranging of sources, from written conventional manuscripts to current interview with Kejawen teachers and opinion leaders which obtained from social media like YouTube. This article found that there are four categories of topics that showcase Kejawen political dimension namely Refusal of Being Categorized as a Religion, Rejection towards Islamization and heretical prejudice, Kejawens Mesianism, and Esoteric approach to Theology.